Antioxidant Effects of Green Tea and Its Polyphenols on Bladder Cells - Coyle, Christian H. (2008)
Genitourinary tract inflammation/ailments affect the quality of life and health of a large segment of society. In recent years, studies have demonstrated strong anti-oxidant effects of green tea and its associated polyphenols in inflammatory states. This in vitro study examined the antioxidant capabilities (and putative mechanisms of action) of green tea extract (GTE), polyphenon-60 (PP-60, 60 % pure polyphenols), (−)-epicatechin-3-gallate (ECG) and (−)-epigallocatechin-3-gallate (EGCG) in normal/malignant human bladder cells following catechin treatment ± 1 mM H(2)O(2) (oxidative agent). Cell viability, apoptosis and reactive oxygen species (ROS) formation were evaluated. Our results showed that H(2)O(2) exposure significantly reduced normal (UROtsa) and high-grade (TCCSUP, T24) bladder cancer (BlCa) cell viability compared with control-treated cells (p < 0.001). No affect on low-grade RT4 and SW780 BlCa cell viability was observed with exposure to H(2)O(2). Compared to H(2)O(2)-treated UROtsa, treatment with PP-60, ECG and EGCG in the presence of H(2)O(2) significantly improved UROtsa viability (p < 0.01), with strongest effects evoked by ECG. Additionally, though not as effective as in UROtsa cells, viability of both high-grade TCCSUP and T24 BlCa cells, in comparison to H(2)O(2) -treated cells, were significantly improved (p < 0.01) by treatment with PP-60, ECG, and EGCG in the presence of H(2)O(2). Overall, our findings demonstrate that urothelium cell death via H(2)O(2)-induced oxidative stress is mediated, in part, through superoxide (O(2)(−·)), and potentially, direct H(2)O(2) mechanisms, suggesting that green tea polyphenols can protect against oxidative stress/damage and bladder cell death.